Media Framing Analysis of Detik.com and Kompas.com in Reporting on the Death of a Family in Kalideres - Emeraldien, Fikry Zahria; Salsabila, Dhea; Aini, Aisyah Nurul; Ubaldo, Emil (Proceedings of International Conference on Da'wa and Communication, 2023)
The mass media has specific objectives in every statement, namely to convince readers to be interested and engage in the discourse provided. The purpose of this research is to describe Robert Entman's framing scheme in the online media Detik.com and Kompas.com in reporting on the investigation process to the announcement of the final results of the case of the family's death in Kalideres. This study focuses on two Detik.com news articles titled "Police Find Clues Regarding the Deaths of a Family in Kalideres" and "Next Week, Police Will Conclude the Mystery of the Deaths of a Family in Kalideres," published on November 15, 2022, and December 4, 2022, as well as two Kompas.com news articles titled "When Police Struggle to Unravel the Mystery of the Deaths of a Family in Kalideres" and "Experts Urge the Police to Immediately Disclose the Deaths of a Family in Kalideres, Even Though Unsolved," published on November 17, 2022, and December 1, 2022. The research method used to analyze the news text is descriptive through Robert Entman's framing analysis. The results of the analysis based on Robert Entman's framing indicate that the online media Detik.com informs that the police can easily find the cause of the family's death in Kalideres. Meanwhile, Kompas.com suggests that the police are having difficulty in solving the case of the family's death in Kalideres. Furthermore, Detik.com also portrays the police as optimistic, responsive, and prompt because they firmly commit to announcing the case of the family's death in Kalideres promptly. In contrast, Kompas.com implicitly states that the police are not acting swiftly in handling the case of the family's death in Kalideres and therefore need to be pressured by psychologists to promptly disclose the investigation results of the case.